Iodine-catalysed N-centered [1, 2]-rearrangement of 3-aminoindazoles with anilines: efficient access to 1, 2, 3-benzotriazines. Issue 1 (11th December 2019) - Ren, Jie; Yan, Xinxin; Cui, Xiaofan; Pi, Chao; Wu, Yangjie; Cui, Xiuling
Abstract : A straightforward and synthetically valuable approach for the synthesis of 1, 2, 3-benzotriazines has been developed via iodine-catalysed N-centered [1, 2]-rearrangement of 3-aminoindazoles with anilines. Abstract : A straightforward and synthetically valuable approach for the synthesis of 1, 2, 3-benzotriazines has been developed via iodine-catalysed N-centered [1, 2]-rearrangement of 3-aminoindazoles with anilines. This reaction tolerated a wide scope of substrates under simple reaction conditions employing I2 as a cheap catalyst.